POTENTIAL EFFECT OF BIS-[(HYDROXYL-NAPHTHALEN-2-YL)-PHENYL-METHYL]-UREA (1,3 BPMU) ON DIETHYL NITROSAMINE (DEN) INDUCED HEPATOCARCINOMA IN WISTAR ALBINO RATS. - VADANASUNDARI VEDARETHINAM; ILAVENIL SOUNDHARAJAN; RAVIKUMAR SIVANESAN (International Journal of Pharma and Bio Sciences, 2014)
Cancer is a leading lethal disease. Hepatocellular carcinoma (HCC) is one of the most common malignant tumors worldwide,Which caused by various factors such as environmental pollutions, Chemical usages, alcohol and Hepatitis B virus (HBV).Now a day researchers involved to develop drug fro HCC.In our present study1,3 –Bis-[(hydroxyl-naphthalen-2-yl)-phenyl-methyl]-urea is a newly synthesized mannich base has showed a wide variety of biological activities for the treatment of oxidative mediated diseases. The present study is aimed to evaluate its receptor binding score value of insilico docking, therapeutic potential of 1, 3BPMU on DEN induced rats were estimated by various biochemical parameters such as total albumin, globulin and bilurubin urea, creatinine enzymatic and non enzymatic antioxidant status in control and experimental rats. 1, 3BPMU treatment significantly normalized the altered biochemical levels and antioxidant activity in DEN induced rats. Further, SEM analysis revealed that the 1, 3BPMU protects the membrane changes induced by the DEN in rats. Therefore, we suggest that 1, 3BPMU could be useful for drug development against Hepatocellular carcinoma.